Analisis Yuridis-Pastoral Pernikahan Usia Dini dalam Terang Kitab Hukum Kanonik No. 1055 dan 1056 pada Pasangan Katolik - Felix Riondi Sugar; Anjelinus Sandri; Marselinus Langgor; Alka Mariano Erwin Saputra; Oktovianus Funan Pineul; Silverius Triwira Juniarto Evan Muda; Dionisius Rienaldi Pea Muga; Chanisio Oktavian Pinanzo (Lembaga Pengembangan Kinerja Dosen, 2026)
Early marriage is a social phenomenon that remains prevalent in Indonesia and gives rise to various problems in family life. This article aims to analyze the implications of early marriage in light of the Code of Canon Law (CCL) Nos. 1055 and 1056 in the context of Catholic couples. This study employs a qualitative method with a descriptive-analytical approach through a literature review of books, scientific journals, and Church documents. The findings indicate that the CIC affirms marriage as a sacred covenant between a man and a woman oriented toward the bonum coniugum (the good of the couple), openness to children, and characterized by unity and indissolubility. In the context of early marriage, various implications were identified, such as emotional immaturity that triggers domestic conflicts, a high risk of divorce, low levels of education, and impacts on the health of mothers and children. Additionally, early marriage also indicates a weak understanding of the sacramental dimension and family responsibilities, including childrearing. Thus, CIC Nos. 1055 and 1056 provide an important normative foundation that marriage requires human, spiritual, and social maturity for the realization of a wholesome and prosperous Catholic family.